Murdoch on ethical formation in a changing world - Hämäläinen, Nora Fiona Karolina (My University, 2022)
In the past few years, we have seen emerging new work that focalizes the role of historical change and its moral implications in Iris Murdoch's philosophy. This paper strengthens this reading of her work and investigates the implications of this aspect of Murdoch's thinking for education in general and for moral education in particular. It resituates the Platonic imagery of the individual's ascent towards the true and the good in a frame where our conceptions of the true and the good are in a process of historical reconfiguration.
Keywords: Iris Murdoch; education; historicity; moral change; conceptual change